Flow behaviour to determine the defects of green part in metal injection molding - Mohamad Nor, Nor Hafiez; Muhamad, Norhamidi; Muhammad Hussain, Ismail; Jamaludin, Khairur Rijal; Sufizar, Ahmad; Ibrahim, Mohd. Halim Irwan (University of Malaya, 2009)
The paper describes author’s work on the investigation of the molding flow behaviour to determine the defects of green part in metal injection molding (MIM) using powder of carbonyl iron (CIP-S-1641) mix with polymer-based binder, Hostamont EK583 at different powder loadings. Rheological properties of the feedstock were presented in this paper. Results show that all feedstock have good pseudoplastic behaviour, which is suitable to be injection molded. Since the flow behaviour of the feedstock in molding cannot solely depends on the rheological test especially in control the quality of green part, this paper also investigate the molding practice via using MOLDFLOW software and compared with the actual experiment. After molding practice the results shows some defects still occurred on green part and it has been control by proposed the optimum molding parameters such as injection temperature and injection pressure.